Oxford textbook of obstetrics and gynaecology - Arulkumaran, Sabaratnam; Ledger, William; Denny, Lynette; Doumouchtsis, Stergios (Oxford university press, 2020)
The Oxford Textbook of Obstetrics and Gynaecology is an up-to-date, objective and readable text that covers the full speciality of Obstetrics and Gynaecology. Edited by a team of four leading figures in the field, whose clinical and scientific backgrounds collectively cover the whole spectrum of Obstetrics and Gynaecology with particular expertise in fetomaternal medicine and obstetrics, gynaecological oncology, urogynaecology, and reproductive medicine, the textbook helps inform and promote evidence-based practice and improve clinical outcomes worldwide across all facets of the discipline. Larger sections on the Basics in Obstetrics and Gynaecology, Fetomaternal medicine, Management of Labour, Gynaecological problems, Gynaecological oncology are complimented by specialist sections on areas such as Neonatal Care & Neonatal Problems, Reproductive medicine, and Urogynaecology and Pelvic Floor Disorders to name a few.